Penanaman Nilai Agama Dan Moral Anak Usia Dini Melalui Metode Pembiasaan - sholikhah, khusnul lailatus; Muzaqi, Sugito (Universitas Narotama, 2024)
This research aims to determine the instillation of religious and moral values in early childhood using the habituation method in Ash - Sholihin Kindergarten. The method used in this research is descriptive qualitative research with data collection techniques of observation, interviews and documentation. There are four habits of instilling religious and moral values in children that have been implemented at Ash - Sholihin Kindergarten, namely routine habits, exemplary habits, spontaneous habits and programmed habits. The success of the habituation method means that children's religious and moral values have begun to develop in Ash - Sholihin Kindergarten, as in the children's daily life at school, children are able to shake hands well, are able to say requests for help, thank you and sorry according to their needs, are able to follow and perform prayers well and are able to applying several daily prayers, and so on. Keywords: Religious and Moral Values, Habituation Method, Early Childhood.